Hypothermia and recovery outcomes before and after implementation of a multimodal perioperative temperature-management bundle in minimally invasive radical rectal cancer surgery - Qian Liu; Ling Liu; Chenxi Han; Chunmei Cao; Jiefang Ji; Aihua Zhu (Frontiers in Oncology, 2026)
Background Inadvertent perioperative hypothermia is common during minimally invasive rectal cancer surgery. We assessed whether a five-component multimodal temperature-management bundle was associated with improved perioperative outcomes. Methods This single-center retrospective before-and-after study included 247 adults undergoing laparoscopic or robot-assisted radical rectal cancer surgery from 2021 to 2025 (pre-implementation, n = 123; post-implementation, n = 124). The primary outcome was any intraoperative nasopharyngeal core temperature <36.0 °C. Key secondary outcomes were minimum temperature, cumulative hypothermia duration, postanesthesia care unit (PACU) stay, shivering, and 30-day composite complications. Prespecified mixed-effects and multiplicity-adjusted analyses were performed. Results Hypothermia occurred in 84/123 patients (68.3%) before implementation and 19/124 (15.3%) after implementation (absolute risk difference, −53.0 percentage points; 95% confidence interval [CI], −62.2 to −41.6; P < 0.001). After implementation, minimum temperature was higher (36.05 ± 0.22 °C vs 35.28 ± 0.62 °C), hypothermia duration was shorter (0 [0–0] vs 42 [0–88] min), PACU stay was shorter (50 [43–60] vs 66 [55–79] min), shivering was less frequent (7.3% vs 42.3%), and composite complications were lower (17.7% vs 36.6%) (all adjusted P ≤ 0.001). The implementation period remained associated with lower hypothermia odds after adjustment (adjusted odds ratio, 0.066; 95% CI, 0.029–0.149). Conclusions Bundle implementation was associated with lower intraoperative hypothermia burden and improved selected recovery outcomes. The nonrandomized calendar-period design and possible secular confounding limit causal interpretation.